Quantum codes from algebraic curves with automorphisms - Shaska, T. (Condensed Matter Physics, 2008)
Let X be an algebraic curve of genus g ≥ 2 defined over a field Fq of characteristic p > 0. From X, under certain conditions, we can construct an algebraic geometry code C. If the code C is self-orthogonal under the symplectic product then we can construct a quantum code Q, called a QAG-code. In this paper we study the construction of such codes from curves with automorphisms and the relation between the automorphism group of the curve X and the codes C and Q. Нехай – алгебраїчна крива типу g ≥ 2, що визначена над полем Fq характеристики p. При деяких умовах на ми можемо будувати алгебраїчно-геометричний код C. Якщо код C є самоортогональним вiдповiдно до симплектичного добутку, то будується квантовий код Q, який будемо називати QAC кодом. В статтi вивчаються конструкцiї таких кодiв за кривими з автоморфiзнами i зв’язки мiж групами автоморфiзмiв кривої та кодiв C та Q.